Hukum Waris Dalam Bisnis Keluarga Syariah: Perencanaan Dan Pengelolaan Aset - Ayunda, Niken Resty; Khairi, Rifqil (EL-EMIR Institute, 2024)
This research aims to analyze the implementation of inheritance law in sharia family businesses, with a focus on success planning and asset management. This research explores how sharia principles are applied in the process of dividing inheritance and how asset management is carried out to ensure the survival and sustainability of family businesses. The method used in this research is a qualitative approach with case studies on several sharia family businesses in Indonesia. Data was collected through in-depth interviews with business owners, heirs, as well as experts in sharia law and asset management. Data analysis was carried out using thematic analysis techniques to identify main patterns and themes related to inheritance planning and asset management in the context of sharia family businesses. The research results show that the implementation of sharia inheritance law in family businesses still faces various challenges, including a lack of understanding of inheritance law, disputes between heirs, and complexity in managing modern business assets. However, with good planning, adequate training, and the implementation of professional management and investment in accordance with sharia principles, family businesses can ensure business continuity and fair distribution of assets in accordance with sharia provisions. This research provides practical recommendations for Muslim families running businesses to optimize their inheritance planning and asset management.